Positive Solutions for the Initial Value Problem of Fractional Evolution Equations - He Yang; Yue Liang (Abstract and Applied Analysis)
By using the fixed point theorems and the theory of analytic semigroup, we investigate the existence of positive mild solutions to the Cauchy problem of Caputo fractional evolution equations in Banach spaces. Some existence theorems are obtained under the case that the analytic semigroup is compact and noncompact, respectively. As an example, we study the partial differential equation of the parabolic type of fractional order.